Stretching the boundaries: the rise and rise of out-of-field teaching in Australia - Ross, Emily; Hobbs, Linda (Curriculum perspectives, 2024)
Teachers are placed in OOF positions for varying reasons: either temporarily or as an expected part of their long-term career trajectory; as either novice or experienced teachers; for varying proportions and frequency within their teaching load; and with varying levels of teacher commitment to the subject long term (Donitsa-Schmidt et al., 2021; Hobbs, 2013, 2020; Nixon et al., 2017). Measurement In Australia, a lack of systematic and system-wide data, particularly in relation to teacher subject specialisations (Weldon, 2016), has led to governments ignoring the growing trend and acceptance of OOF teaching as a solution to long-term teacher shortages. Research acknowledges that OOF teachers are a heterogeneous group (Hobbs, 2020; Sharplin, 2014). [...]their support needs and willingness to continue to teach the OOF subject and seek additional qualifications vary (Hobbs & Törner, 2019). Data collection can focus on teacher qualifications, the lived experience of teachers, and a way of understanding the impacts.